GSB CULTURE IN PROVERBIAL PERSPECTIVE: A STUDY ON MIGRATION, MYTHS, AND CULTURAL HERITAGE - Shenoy, Aiswaryalakshmi S; Purushothaman, Kavya (International Journal of Research -GRANTHAALAYAH, 2025)
The paper explores proverbial traditions of Gowda Saraswat Brahmin (GSB) community by focusing more on to the migration, history, mythology and identity. Proverbs are one of the important sources for passing down expressions and values especially it can also be used as a tool to analyse the socio-cultural background of particular community as it is mostly used in daily routine. GSB or Gowda Saraswat Brahmins are widely recognised brahmin clan in India. They are embedded with large cultural values and strongly believe in Dhrama.A key challenge for language preservation is the gradual loss of oral storytelling conventions put on by lack of written documents. Researching Konkani proverbs shows the expanded narratives of myth migration and culture One of the oldest and most efficient ways for preserving and transmitting down culture from one generation to the next is language. It serves as a storehouse of a community's identity, traditions, beliefs, and collective memory. Linguistic preservation is crucial for conserving the variety of a society's customs, beliefs, and narratives of history due to the loss of a language often ends in a destruction of cultural tradition and this paper helps to recollect these cultures through recording and analysing some of the daily used proverbs in Konkani.